Optimizing Online Business Security with Blockchain Technology - Nyree Ani; Shofiyul Millah; Po Abas Sunarya (Pandawan Sejahtera Indonesia, 2024)
This research discusses the implementation of blockchain technology to improve online business security. The main problem facing online businesses today is their vulnerability to security attacks such as data theft and information leaks. The aim of this research is to optimize online business security by utilizing the advantages of blockchain technology in providing data security, integrity, and transparency. This research method includes a literature review to understand existing online business security frameworks and analysis of possible weaknesses. Next, we designed and implemented a blockchain-based solution to mitigate the identified security risks. Data collection is carried out through security attack simulations and reliability testing of the proposed system. The research results show that the application of blockchain technology significantly increases the security of online businesses, reduces the risk of data theft, and provides a high level of transparency. The conclusions of this research support the view that blockchain can be an effective solution to overcome security problems in the context of online business. This research makes a significant contribution to understanding and applying blockchain technology as an innovative security solution in the context of online business.